Implementasi Media Ajar Roda Baca untuk Proses Membaca Permulaan Peserta Didik Kelas 1 SDS Wahidiyah : Desa Tugu Kecamatan Sendang Kabupaten Tulungagung - Asma Hanny Thohiroh; Yasip Yasip; Rahyu Setiani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the early reading skills of first-grade students at Wahidiyah Elementary School in Tugu Village, Sendang District, Tulungagung Regency. This study uses a qualitative approach with a model adapted from John Creswell. The research subjects consisted of five students selected purposively. Data collection techniques were carried out through observation, interviews, and documentation. The focus of the study was directed at five indicators of early reading, namely: letter recognition, syllable recognition, combining letters into words, reading words, and reading simple sentences. The results of the study showed that the use of the reading wheel teaching media had a positive impact on improving students' early reading skills. Students appeared enthusiastic about participating in reading learning activities with the reading wheel media. The activity of spinning the wheel, arranging letters, and reading the results of the rotation became a fun learning tool and motivated them to be more active. This process helped students recognize letters and put words together gradually, although the achievement of each student's early reading skills varied. The reading wheel teaching media was proven to create an interactive and enjoyable learning atmosphere. The conclusion of this study is that the reading wheel media is effective for use in early reading learning in first-grade elementary schools. Researchers recommend that teachers develop and utilize similar innovative teaching media to support students' early literacy skills.